„Czadowy” życiorys bohatera drogi, czyli komparatystyczne spojrzenie na Moskwę-Pietuszki Wieniedikta Jerofijewa i Jak zostałem pisarzem Andrzeja Stasiuka - Waligórska-Olejniczak, Beata (Acta Polono-Ruthenica, 2011)
In the context of postmodern culture J. Lotmans notion of the hero on the road seems to be the most adequate and up-to-date representation of the contemporary human being. Moscow Petushki of V. Yerofeyev and How I Became a Writer of A. Stasiuk constitute the examples of novels whose plot is built up around travel, adventures and protagonists movement between the points in the topography of a city or country. However, the heros peregrination in both text is meant to be just background and inspiration for the core element of the works, which is metaphysi- cal reflection on life. The article tries to present the characters of the above mentioned works as the complementary variations of the nomadic hero which results in treating them as the creative commentary to understanding Polish and Russian mentality. The discussion focuses on such analogies in the texts as social and intellectual background of the protagonists, their attitute to the communist reality revealed in their showing disrespect to the system, independence manifested through the body language or indifference towards the government. Both texts can amuse the reader with sophisticated recipies for alcoholic coctails which have to be consumed to survive everyday reality. The space in Yerofeyevs text, apart from the mythical Petushki, seems to be more neutral or sometimes even hostile, the landscape in Stasiuks novel is shaped by the memo- ries of the hero, his experiences make it more local, easy to recognize and familiarize.